The Effect of The Thinking Aloud Pair Problem Solving (TAPPS) Learning Model Assisted by Domino Cards on Students' Learning Outcomes in Economics at SMA Negeri 8 Palembang - Aan Nugraha; Erma Yulaini; M. Toyib (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2026)
This study was undertaken in response to the relatively low level of students' learning outcomes, which was attributed to the continued implementation of conventional instructional approaches at SMA Negeri 8 Palembang. The research aimed to investigate the effectiveness of the Thinking Aloud Pair Problem Solving (TAPPS) learning model supported by domino cards in improving students' achievement in Economics. A quantitative approach with a Quasi-Experimental Design, specifically the Posttest-Only Control Group Design, was employed. The study involved 68 students selected through simple random sampling, comprising Class X.1 as the experimental group and Class X.2 as the control group. Data were gathered through classroom observations and posttest assessments, and subsequently analyzed using tests of normality and homogeneity, the Independent Samples t-test, and effect size analysis. The findings revealed that students in the experimental group achieved a higher average posttest score (84.56) than those in the control group (82.94). Furthermore, the hypothesis testing produced a significance value of 0.029 (< 0.05), indicating that the implementation of the TAPPS learning model assisted by domino cards had a statistically significant effect on students' learning outcomes. Nevertheless, the calculated effect size was 0.15, which is categorized as very small, implying that although the intervention demonstrated statistical significance, its practical contribution remained limited. These findings suggest that the TAPPS learning model assisted by domino cards can be considered a viable alternative instructional strategy for enhancing Economics learning.